Прогностическая роль циркулирующего N-терминального фрагмента промозгового натрийуретического пептида у пациентов после лечения множественной миеломы - Самура, Б. Б.; Самура, Борис Борисович; Samura, B. B. (My University, 2017)
Целью настоящего исследования было выявление прогностической значимости циркулирующего N-терминального фрагмента промозгового натрийуретического пептида (NT-pro-МНУП) в возникновении кардиоваскулярных событий у пациентов после лечения множественной миеломы. Материалы и методы. В исследование были включены 89 пациентов после лечения множественной миеломы, период наблюдения составил 12 месяцев. Забор плазмы крови производился для определения уровня циркулирующего NT-pro-МНУП с помощью иммуносорбентного метода. Результаты. Было зафиксировано 92 кардиоваскулярных события у 36 пациентов (40,5 %): 8 смертей вследствие кардиоваскулярной причины, 46 кардиальных аритмий, 6 кардиальных ишемических событий, 2 инсульта, 8 случаев возникновения хронической сердечной недостаточности, 22 госпитализации, связанные с кардиоваскулярными причинами. Медиана циркулирующего NT-pro-МНУП у пациентов без кардиоваскулярных событий составила 5,68 пг/мл (95% ДИ — 2,74–11,51 пг/мл), у пациентов с кардиоваскулярными событиями — 23,87 пг/мл (95% ДИ 8,22–31,84 пг/мл) (р = 0,06). Мультивариантный регрессионный анализ показал, что циркулирующий NT-pro-МНУП является независимым прогностическим фактором возникновения кардиоваскулярных событий (отношение шансов OШ = 1,06; 95% ДИ 1,03–1,17; р < 0,01) на протяжении 1 года. В то же время наличие сахарного диабета, артериальной гипертензии, ожирения не показало прогностической значимости. Выводы. Установлено, что среди пациентов после лечения множественной миеломы с достижением ремиссии повышение содержания циркулирующего NT-pro-МНУП может ассоциироваться с увеличением числа кумулятивных кардиоваскулярных событий в течение 1 года. Метою цього дослідження було виявлення прогностичної значущості циркулюючого N-термінального фрагменту промозкового натрійуретичного пептиду (NTpro- МНУП) у виникненні кардіоваскулярних подій у пацієнтів після лікування множинної мієломи. Матеріали та методи. У дослідження були включені 89 пацієнтів після лікування множинної мієломи, період спостереження становив 12 місяців. Забор плазми крові проводили для визначення рівня циркулюючого NT-pro-МНУП за допомогою імуносорбентного методу. Результати. Було зафіксовано 92 кардіоваскулярні події у 36 пацієнтів (40,5 %): 8 смертей з кардіоваскулярної причини, 46 кардіальних аритмій, 6 кардіальних ішемічних подій, 2 інсульти, 8 випадків виникнення хронічної серцевої недостатності, 22 госпіталізації, пов’язані з кардіоваскулярними причинами. Медіана циркулюючого NT-pro-МНУП у пацієнтів без кардіоваскулярних подій становила 5,68 пг/мл (95% довірчий інтервал (ДІ) — 2,74–11,51 пг/мл), у пацієнтів з кардіоваскулярними подіями — 23,87 пг/мл (95% ДІ 8,22–31,84 нг/мл) (р = 0,06). Мультиваріантний регресійний аналіз показав, що циркулюючий NT-pro-МНУП є незалежним прогностичним фактором виникнення кардіоваскулярних подій (відношення шансів 1,06; 95% ДІ 1,03–1,17; р < 0,01) протягом 1 року. Водночас наявність цукрового діабету, артеріальної гіпертензії, ожиріння не показало прогностичної значущості. Висновки. Встановлено, що серед пацієнтів після лікування множинної мієломи підвищення рівня циркулюючого NT-pro-МНУП може асоціюватися з виникненням кумулятивних кардіоваскулярних подій протягом 1 року. Multiple myeloma is one of the most common lymphoid malignancies. The introduction of immunomodulatory agents and proteasome inhibitors has improved the survival of patients with this disease, including elderly subjects. However, there is a subgroup of frail subjects, most of whom are elderly, who are susceptible to side effects of chemotherapy and are often unable to tolerate full dose treatment. Little is known about the long-term cardiovascular status of intensively treated survivors. Brain natriuretic peptide and the N-amino terminal fragment of the pro-hormone brain natriuretic peptide (NT-proBNP) are released predominantly from the ventricular myocardium in response to increased ventricular wall stress. They are measures of ventricular dysfunction and have a predictive utility for cardiovascular events and mortality, but because they are cleared by the kidneys, this influences the glomerular filtration rate. Moreover, the prognostic value of NT-proBNP has been shown to be independent of traditional cardiovascular risk factors, prevalent cardiovascular disease, left ventricular dysfunction, and renal function. We purposed to evaluate the prognostic value of circulating NT-proBNP in patients after treatment of multiple myeloma. Materials and methods. Eighty nine subjects after treatment of multiple myeloma were enrolled in the study. Diagnosis and staging of multiple myeloma were defined by current clinical practice guidelines. To achieve the remission, chemotherapy with bortezomib, thalidomide, dexamethasone, cyclophosphamide was used according to the contemporary clinical guidelines. All subjects were at full or partial remission stage at baseline. Observation period was up to 12 months. Blood samples for biomarkers measurements were collected. ELISA method was used for measurements of circulating level of NT-proBNP. Echocardiography in B-mode was performed following the recommendations of American Society of Echocardiography on MyLab 50 scanner (Italy) using a transducer with a frequency of 2.5–3.5 MHz. Results. During observation period, the progression of multiple myeloma was proved in 23 patients, 4 persons were excluded due to poor follow- up. Ninety two cumulative clinical events occurred in 36 patients (40.5 %) within the follow-up, with their distribution being as follows: 8 cardiovascular deaths, 46 cardiac arrhythmias, 8 cardiac ischemic events, 2 strokes, 8 chronic heart failures and 22 hospital admissions for cardiovascular causes. Medians of circulating levels of NT-proBNP in free-events subject cohort and subjects cohort with cardiovascular events were 5.68 pg/ml (95% confidence interval (CI) = 2.74–11.51 pg/ml) and 23.87 pg/ml (95% CI = 8.22–31.84 pg/ml) (р = 0.06). In multivariate logistic regression, circulating NT-proBNP independently predicted cumulative cardiovascular events (odds ratio = 1.06; 95% CI = 1.03–1.17; р < 0.01) within 12 months of observation period. Conclusions. Among patients after treatment of multiple myeloma, increased circulating NT-proBNP may associate with increased cumulative cardiovascular events during 12 months.
Прогностична роль циркулюючого N-термінального фрагменту промозкового натрійуретичного пептиду в пацієнтів після лікування множинної мієломи
Predictive value of N-terminal pro-brain natriuretic peptide in patients after treatment of multiple myeloma
Keywords: NT-pro-МНУП; кардиоваскулярные события; множественная миелома; прогноз; кардіоваскулярні події; множинна мієлома; NT-proBNP; cardiovascular events; multiple myeloma; prognosis